Titanium miniplate fixation in 6-month-old infant with parasymphysis fracture: a case report - Sai Kumar, C.; Haobijam, Nabakishor; Kumar, Prashant; Pillai, Karthika Sobha; Shah, Siddharth (International Surgery Journal, 2025)
Mandibular fractures in infants are uncommon and challenging due to ongoing facial growth and the presence of developing tooth buds. We report a case of a 6-month-old infant with a parasymphysis mandibular fracture managed with open reduction and internal fixation using a titanium miniplate. Surgery was performed with caution to avoid damage to dental structures, and the plate was removed after three months. Follow-up showed normal growth and dental development without complications. This case demonstrates that with proper technique and timing, rigid fixation can be safely used in infants, ensuring both functional recovery and normal craniofacial development.